Wie eindeutig ist ein Kunstwerk?: [Hans Holbein d.J., Francisco Goya, Edouard Manet, Cy Twombly, Philip Johnson, Joseph Beuys] - Imdahl, Max; Busch, Werner (DuMont, 1986)
Literaturangaben
Literaturangaben
Keywords: Aufsatzsammlung; Kunstbetrachtung